Tari Gajah Barong Sebagai Upaya Pelestarian dan Eksistensi Cerita Masyarakat Lokal di Baregbeg, Kabupaten Ciamis - Hervista, Ghea Andriyani (Jurnal Artefak, 2025)
Gajah Barong Dance is a traditional art from Baregbeg, Ciamis Regency, which contains elements of folklore, myth, and local culture. This study aims to examine the history, transformation process, and meaning of Gajah Barong Dance in the lives of local people. The method used in this research is a qualitative approach with a descriptive-interpretative approach, through observation, literature study and documentation, to gain an in-depth understanding of this dance. The results showed that Gajah Barong Dance not only functions as entertainment, but also as a means of preserving local cultural values and local community identity. Its transformation process from oral story to performing art reflects the dynamics of an evolving culture. The implications of this research emphasize the importance of preserving traditional arts as part of Indonesia's cultural diversity. Therefore, it is recommended that there be strategic efforts in supporting the sustainability of Gajah Barong Dance through education, documentation, and revitalization of performances in various media.